A simple, fast and cost-effective method of synthesis of cupric oxide nanoparticle with promising antibacterial potency: Unraveling the biological and chemical modes of action - Chakraborty, Ruchira; Sarkar, Raj Kumar; Chatterjee, Arijit Kumar; Manju, Unnikrishnan; Chattopadhyay, Asoke Prasun; Basu, Tarakdas (Biochimica et biophysica acta, 2015)
Gradual attainment of bacterial resistance to antibiotics led us to develop a robust method of synthesis of stable, colloidal cupric oxide nanoparticle of physiological pH with potential antibacterial action. Cu(II) oxide NP was synthesized by reduction-oxidation of CuCl2, using polyvinyl alcohol as stabilizer. Characteristics and antibacterial activity of the particles were investigated by techniques like UV-Vis spectrophotometry, DLS, AFM, TEM, EDS, FTIR, AAS, agar plating, FACS, gel electrophoresis and XPS. The NPs were about 50 nm in size and cubic in shape with two surface plasmon peaks at 266 and 370 nm and had semi-conducting behavior with a band gap of 3.40 and 3.96 eV. About 80% of precursor CuCl2 was converted to NP. The minimum inhibitory and the minimum bactericidal concentrations of CuO-NP were respectively 120 and 160 μg/mL for Escherichia coli and 180 and 195 μg/mL for Staphylococcus aureus in Luria-Bertani medium. In growth media, the NPs got modified by media organics with displacement of the stabilizer PVA molecules. This modified NP (around 240 nm) killed cells by generating ROS, which finally caused membrane lipid per-oxidation and chromosomal DNA degradation in NP-treated cells. Reports indicate that we are among the few who had prepared CuO-NP in colloidal form. The antibacterial potency of our particle in growth media was much promising than other reports. Our findings demonstrated that 'particle-specific' effect, not 'ion-specific' one, was responsible for the NP action. The NP may be used as a sterilizing agent in various bioprocesses and as substituent of antibiotics, after thorough toxicological study.